Transforming Adult Education in the 21st Century through Artificial Intelligence in Nigeria: Innovation, Impacts, and Ethical Considerations - Okafor, I. M. (Journal of Research in Adult and Continuing Education, 2025)
The 21st century has witnessed a significant transformation in socio-economic, politics, religion, commerce and particularly adult education which is driven by technological innovations, advancements and modernization. Artificial Intelligence (AI) has emerged as a major innovation in adult education, offering personalized learning experiences, feedback mechanism, adaptive assessments, accessibility and enhanced learner-centered engagement and participation. This article explores the potential of AI in transforming adult education in Nigeria, the challenges and its impact on learning outcomes, and ethical considerations that arise. Finding revealed that AI is an inevitable modernization and transformation in all human endeavors particularly in adult education by providing tailored learning pathway, improving accessibility, proximity, and fostering lifelong learning at the comfort of the learners. The paper reveals that transformation of adult education in Nigeria through AI driven education would reduce educational inequality and digital illiteracy, increase access to teaching and learning, instill managerial skills, solve personal problems, enhance lifelong activities, and reduce illiteracy both in the urban and rural areas. On the basis of this, the paper recommended the need for careful consideration of ethical issues, such as data privacy, bias, and transparency among others.
Keywords: Transformation; Adult Education; Artificial Intelligence; Innovation; Impact; Ethical Considerations